The Influence of Health Education Through Audiovisual Media on the Implementation of Eye Exercises on Teenagers - Wahyuningsih, Binarti Dwi (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
This outreach aims to prove the influence of health education through audiovisual media on implementing eye exercises among teenagers at SMAN XI Surabaya. The socialization method is to provide health education through audiovisual for implementing eye exercises for teenagers at SMAN XI Surabaya. The implementation of the activity began with providing counseling using the lecture method, democracy, and showing videos about eye exercises. Almost all of the implementation of eye exercises after being given health education was in a good category with 23 respondents (92%). The increase in respondents' ability to do eye exercises was due to the respondents having been given health education. So, it can be concluded that delivering health education using audiovisual media can provide a lot of stimulus to students, because the nature of audiovisuals combines sound and images, making it easier for students to do eye exercises independently.